Impact of protocolized fluid management on electrolyte stability in patients undergoing continuous renal replacement therapy - Baeg, Song In; Jeon, Junseok; Kang, Danbee; Na, Soo Jin; Cho, Juhee; Kim, Kyunga; Yang, Jeong Hoon; Chung, Chi Ryang; Lee, Jung Eun; Huh, Wooseong; Suh, Gee Young; Kim, Yoon-Goo; et al. (Frontiers in Medicine, 2022)
Objective: Continuous renal replacement therapy (CRRT) is the standard treatment for critically ill patients with acute kidney injury. Electrolyte disturbance such as hypokalemia or hypophosphatemia occurs paradoxically in patients undergoing CRRT due to high clearance. We developed a fluid management protocol for dialysate and replacement fluid that depends on serum electrolytes and focuses on potassium and phosphate levels to prevent electrolyte disturbance during CRRT. The impact of our new fluid protocol on electrolyte stability was evaluated. Methods: Adult patients who received CRRT between 2013 and 2017 were included. Patients treated two years before (2013 to 2014; pre-protocol group) and two years following development of the fluid protocol (2016 to 2017; protocol group) were compared. The primary outcomes were individual coefficient of variation (CV) and abnormal event rates of serum phosphate and potassium. Secondary outcomes were frequency of electrolyte replacement and incidence of cardiac arrhythmias. Individual CV and abnormal event rates for each electrolyte were analyzed using the Wilcoxon rank-sum test and Chi-square test with Yates’ continuity correction. Results: A total of 1448 patients was included. Both serum phosphate and potassium were higher in the protocol group. The CVs of serum phosphate (pre-protocol vs. protocol, 0.275 [0.207-0.358] vs. 0.229 [0.169-0.304], p<0.01) and potassium (0.104 [0.081-0.135] vs. 0.085 [0.064-0.110], p<0.01) were significantly lower in the protocol group. The abnormal event rates of serum phosphate (rate [95% CI], 0.410 [0.400-0.415] vs. 0.280 [0.273-0.286], p<0.01) and potassium (0.205 [0.199-0.211] vs. 0.083 [0.079-0.087], p <0.01) were also significantly lower in the protocol group. Conclusions: The protocolized management of fluid in CRRT effectively prevented hypophosphatemia and hypokalemia by inducing excellent stability of serum phosphate and potassium levels.